Contacting surface-transfer control for reconfigurable wall-climbing robot gunryu III - Lee, W.; Hirose, S. (Fuji Technology Press, 2013)
For the wall-climbing robots, high mobility as well as stability on the surface of the walls are the most important features. To achieve these features, this paper proposes a new type of reconfigurable arm equipped multi module wall-climbing robot named Gunryu III. Gunryu III has the potential ability to generate high stability and high mobility by using its arm to connect multiple mobile modules together and a magneticforce-changeable adsorption device. One of the important motions of the reconfigurable wall-climbing robot Gunryu III is surface-transfer motion, which is to change from one moving surface to another, such as from floor to wall and wall to ceiling. In this paper, we propose a new surface-transfer motion strategy named Contact Mode. It is to make surface-transfer motion by contacting some part of the moving module to one of the surfaces. As for the Contact Mode surfacetransfer motion, we first conduct several fundamental discussions, such as the five basic types of motion, conditions for making contact between the mobile module and the wall, effective way of using the magnetic device and two criteria of the evaluation. We then quantitatively evaluate the effectiveness of the proposed Contact Mode surface-transfer motion using simulation experiments, and clarify basic optimized control strategies.
Keywords: Intelligent robots; Mobile robots; Permanent magnets; Contact modes; Contacting surfaces; Gunryu III; Important features; Optimized control; Potential ability; Reconfigurable robot; Wall climbing robot; Robot applications